Granivorous birds in ecosystems - Turček, František J. (Zielona Góra: University of Zielona Góra, Faculty of Biological Sciences)
Granivorous birds are considered to be species which feed on seeds, droplets and fruits of plants in general. Not enclosed in such a definition, however, is feeding on (or the transportation of) pollen, although pollen of a number of plant species is able to germinate or produce seedlings. Our knowledge about this specific relationship of birds and plants and about their respective impact on ecosystems, however, is like the jaw of a rodent - there are more gaps than teeth. The present and rather short paper deals only with European birds (391 species) and ecosystems. Therefore, the conclusions made do not exclude other generalizations.
Keywords: wróblowe; ornitologia